Solid electrolyte film, preparation method thereof and all-solid-state battery

By adding second phase inorganic materials, such as LiFSI and KFSI, to the solid electrolyte membrane layer of an all-solid state battery, the hole defects are filled with their phase change properties, the problem of poor density of the solid electrolyte membrane layer is solved, and a high density and low cost solid electrolyte film preparation is achieved, reducing the risk of battery short circuit.

CN119601755APending Publication Date: 2025-03-11CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411673236.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

全固态电池中固体电解质膜层的孔隙度高,导致锂枝晶的随机形成和电池短路失效,现有技术难以保证膜层的致密性,且工艺难度大、成本高,产品质量难以控制。

Method used

The density of the solid electrolyte film is increased by adding the second phase inorganic material, such as LiFSI and KFSI, to the electrolyte powder, and using its melting and flow during hot pressing, filling hole defects.

Benefits of technology

The basic complete density of the solid electrolyte film is achieved, the risk of short circuit of all solid state batteries is reduced, and the preparation method is simple to operate and low cost, and high ionic conductivity is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601755A_ABST
    Figure CN119601755A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte film, a preparation method thereof and an all-solid-state battery, and the method comprises the following steps: mixing a solid electrolyte and a second-phase inorganic material to obtain mixed powder; wherein the mass ratio of the solid electrolyte to the second-phase inorganic material is 1: (0.1 wt%-30 wt%); dispersing the mixed powder and a binder into an organic solvent to obtain solid electrolyte slurry; and carrying out coating treatment, drying treatment and hot pressing treatment on the solid electrolyte slurry to obtain a completely compact and void-free solid electrolyte film. According to the solid electrolyte film disclosed by the invention, the second phase inorganic material can be quickly molten during heating and can flow during pressurization, so that the second phase inorganic material can fill holes in defects in the electrolyte powder film layer, and the density of the electrolyte film layer can be improved. And secondly, the method has the advantages of simplicity in operation and low cost, the original high ionic conductivity can be maintained, and the short-circuit risk of the all-solid-state battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of all-solid-state batteries, and specifically to a solid electrolyte film and a preparation method thereof, and an all-solid-state battery. Background Art

[0002] As one of the most promising batteries, the technical level of all-solid-state lithium batteries is still in its early stages from the perspective of battery energy density and scalable manufacturing. Among them, the ultra-thin solid electrolyte film layer in all-solid-state batteries is the most core process difficulty. Most of the research focuses on depositing a solid electrolyte layer on the active material by a wet method, that is, a thin electrolyte layer is obtained by mixing a binder, a solvent, and an electrolyte powder into a slurry and coating it. However, the shrinkage phenomenon of the electrolyte membrane prepared by the above method during slurry drying will lead to the appearance of pinholes; in addition, during isostatic pressing, due to limited pressure and temperature, large grain boundaries or three-dimensional defects will also appear in the film layer. Since all-solid-state batteries cannot control the random formation of lithium dendrites during the charge / discharge cycle, lithium dendrites will grow through the above pinholes and three-dimensional defects, further causing battery short circuit failure and thermal runaway.

[0003] In order to solve the problem of high porosity of the electrolyte layer, the prior art uses a solvent to wet-coat sulfide or oxide solid electrolyte particles with a thermoplastic resin to prepare a composite material, and hot-presses the composite material at a relatively low temperature and low pressure, but this method cannot guarantee that the film layer is almost completely dense. The prior art also combines lithium, sulfur and boron precursor materials to form a precursor mixture, melts the mixture, and then pulls the molten glass into a strip and quenches it to form thin glass. However, this method is not only difficult to process, the cost is too high, and the product quality is difficult to control, but it is completely impossible to achieve a balance between the difficulty of the preparation process, the conductive performance and the battery price. Therefore, there is an urgent need for a solid electrolyte film with low preparation difficulty and easy cost control and a preparation method thereof to solve the porosity problem on the surface of the solid electrolyte membrane. Summary of the invention

[0004] In order to solve the above technical problems, the present application proposes a solid electrolyte film and a preparation method thereof, and an all-solid-state battery. The preparation method of the present invention adds a second-phase inorganic material to the electrolyte powder, and can utilize the second-phase inorganic material to melt quickly when hot-pressed and flow when pressurized, so that it can fill the defects in the electrolyte powder film layer, thereby improving the density of the solid electrolyte film.

[0005] On the one hand, an embodiment of the present application provides a method for preparing a solid electrolyte film, the preparation method comprising:

[0006] The solid electrolyte and the second-phase inorganic material are mixed to obtain a mixed powder; in the mixed powder, the mass ratio of the solid electrolyte to the second-phase inorganic material is 1: (0.1wt% to 30wt%);

[0007] Dispersing the mixed powder and the binder in an organic solvent to obtain a solid electrolyte slurry;

[0008] The solid electrolyte slurry is subjected to coating treatment, drying treatment and hot pressing treatment to obtain the solid electrolyte film.

[0009] Further, the second phase inorganic material includes at least one of LiFSI and KFSI;

[0010] In the case where the second-phase inorganic material includes LiFSI and KFSI, a molar ratio of the LiFSI to the KFSI ranges from (0 to 100): (100 to 0).

[0011] Further, in the case where the second-phase inorganic material includes the LiFSI and the KFSI, before the solid electrolyte slurry is subjected to coating, drying and hot pressing to obtain the solid electrolyte film, the method further includes:

[0012] determining a molar ratio of the LiFS I and the KFS I;

[0013] determining a melting point of the second phase inorganic material based on a molar ratio of the LiFS I to the KFS I;

[0014] Based on the melting point, the hot pressing method and corresponding hot pressing parameters are determined; the hot pressing method includes at least one of roller pressing, flat plate pressing, and isostatic pressing.

[0015] Furthermore, the hot pressing parameters corresponding to the flat plate pressing and the isostatic pressing include hot pressing temperature, hot pressing pressure and hot pressing time; the hot pressing temperature is 70°C to 130°C; the hot pressing pressure is 100MPa to 1000MPa; the hot pressing time is 1min to 100min;

[0016] The hot pressing parameters corresponding to the rolling include rolling pressure and rolling temperature; the rolling pressure is 10 kN / m to 150 kN / m; and the rolling temperature is 70° C. to 130° C.

[0017] Furthermore, the sum of the masses of the binder and the mixed powder is a first mass, and the mass of the binder accounts for 0.1% to 5% of the first mass.

[0018] Furthermore, the solid content of the solid electrolyte slurry is 20% to 80%, and the mixed powder and the binder are dispersed in an organic solvent to obtain the solid electrolyte slurry, comprising:

[0019] Determining the mass of the organic solvent as the second mass according to the solid content, the mass of the mixed powder and the mass of the binder;

[0020] Mixing the mixed powder and the binder to obtain electrolyte powder;

[0021] The electrolyte powder is dispersed in a second mass of an organic solvent to obtain the solid electrolyte slurry.

[0022] Furthermore, the solid electrolyte includes Li2ZrCl6, LiNbOCl4, LiTaOCl4, Li3YCl6, Li3InCl6, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li10GeP2S12, Li2S-SiS2-Li x MO y , Li2S-P2S5-Z m S n At least one of; wherein x and y are positive numbers, M is one of P, Si, Ge, B, Al, Ga and In; m and n are positive numbers, Z is one of Ge, Zn and Ga.

[0023] Furthermore, the binder includes at least one of styrene-butadiene rubber, polyacrylonitrile-butadiene, styrene-ethylene-butylene-styrene block copolymer, and styrene-ethylene-propylene-styrene block copolymer.

[0024] On the other hand, an embodiment of the present application further provides a solid electrolyte film, which is obtained by the above-mentioned method for preparing a solid electrolyte film.

[0025] On the other hand, an embodiment of the present application also provides an all-solid-state battery, which includes the above-mentioned solid electrolyte film.

[0026] The present application provides a solid electrolyte film and a preparation method thereof, and an all-solid-state battery. Compared with the prior art, the present invention has the following beneficial technical effects:

[0027] 1. The embodiment of the present application adds a second-phase inorganic material to the electrolyte powder, and uses the phase change method of the second-phase inorganic material to improve the density of the solid electrolyte film. Specifically, the second-phase inorganic material can melt quickly when heated and flow when pressurized, so that it can fill the defects in the electrolyte powder film layer, thereby improving the density of the solid electrolyte film and obtaining a substantially completely dense, void-free solid electrolyte film layer, thereby reducing the short circuit risk of the all-solid-state battery.

[0028] 2. The preparation method provided in the embodiment of the present application has the advantages of simple operation and low cost, and will not affect the high resistance phase inside the solid electrolyte film, basically maintaining the original high ionic conductivity, and can also reduce the short circuit risk of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 It is a schematic flow chart of a method for preparing a solid electrolyte film provided in an embodiment of the present application;

[0031] Figure 2 It is a schematic flow chart of a method for preparing a solid electrolyte slurry provided in an embodiment of the present application;

[0032] Figure 3 It is a flow chart of a method for determining a hot pressing treatment provided in an embodiment of the present application;

[0033] Figure 4 is a structural schematic diagram of an all-solid-state battery provided in an embodiment of the present application;

[0034] Figure 5 is a SEM image of a dry film in a solid electrolyte film preparation process provided in an embodiment of the present application;

[0035] Figure 6 This is a SEM image of a dry film in a solid electrolyte film preparation process without adding a second phase inorganic material provided in an embodiment of the present application;

[0036] Figure 7is a SEM image of a solid electrolyte film provided in an embodiment of the present application;

[0037] Figure 8 This is a SEM image of a solid electrolyte film without adding a second phase inorganic material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0038] The following will be combined with exemplary drawings to clearly and completely describe the exemplary technical solutions. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0039] In the field of all-solid-state batteries, the inorganic non-metallic solid electrolyte powders currently commonly used can only undergo limited plastic deformation below the melting point, which makes it impossible to obtain an inorganic electrolyte film layer without micro-nano pores by applying pressure.

[0040] Based on this, Figure 1 As shown, the embodiment of the present application provides a method for preparing a solid electrolyte film, the preparation method comprising:

[0041] S10: mixing a solid electrolyte and a second-phase inorganic material to obtain a mixed powder; in the mixed powder, a mass ratio of the solid electrolyte to the second-phase inorganic material is 1: (0.1 wt% to 30 wt%).

[0042] In an exemplary embodiment, the solid electrolyte and the second-phase inorganic material are weighed as preparation raw materials in a mass ratio of 1: (0.1 wt% to 30 wt%), wherein the solid electrolyte and the second-phase inorganic material are in a powder state.

[0043] The second phase refers to all other phases in the material that are different from the matrix phase. Generally, they are distributed discontinuously in the matrix phase. The second inorganic material refers to the material that has the properties of the second phase and is an inorganic material.

[0044] In some embodiments, the solid electrolyte includes Li2ZrCl6, LiNbOCl4, LiTaOCl4, Li3YCl6, Li3InCl6, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li10GeP2S12, Li2S-SiS2-Li x MO y , Li2S-P2S5-Z m S n At least one of; wherein x and y are positive numbers, M is one of P, Si, Ge, B, Al, Ga and In; m and n are positive numbers, Z is one of Ge, Zn and Ga.

[0045] Optionally, the mixing method can be any one of ultrasound, stirring or ball milling. Preferably, ball milling is used. When ball milling is used for mixing, the ball milling parameters can be: 0.1-5h, rotation speed 100-500rpm, temperature room temperature.

[0046] S30: dispersing the mixed powder and the binder into an organic solvent to obtain a solid electrolyte slurry.

[0047] In some embodiments, the binder includes at least one of styrene-butadiene rubber, polyacrylonitrile-butadiene, styrene-ethylene-butylene-styrene block copolymer, and styrene-ethylene-propylene-styrene block copolymer.

[0048] In some embodiments, the sum of the masses of the binder and the mixed powder is a first mass, and the mass of the binder accounts for 0.1% to 5% of the first mass.

[0049] In some embodiments, the solid content of the solid electrolyte slurry is 20% to 80%.

[0050] Exemplarily, before configuring the solid electrolyte slurry, it is necessary to determine the mass of each component in the solid electrolyte slurry. First, based on the solid content, determine the content of all solid components in the solid electrolyte slurry. Exemplarily, the solid components include a solid electrolyte and a binder. Therefore, the total mass of the solid electrolyte and the binder can be determined based on the first mass, and then the mass of the binder and the mass of the solid electrolyte can be determined based on the mass of the bonding accounting for 0.1% to 5% of the first mass.

[0051] Furthermore, if Figure 2 As shown, the above step S30 includes:

[0052] S31: Determine the mass of the organic solvent as the second mass according to the solid content, the mass of the mixed powder and the mass of the binder.

[0053] S32: Mixing the mixed powder and the binder to obtain electrolyte powder.

[0054] S33: dispersing the electrolyte powder into a second mass of an organic solvent to obtain the solid electrolyte slurry.

[0055] For example, the mass of the organic solvent, i.e., the second mass, can be determined according to the solid content, the mass of the mixed powder and the binder. After the mixed powder and the binder are mixed, the electrolyte powder is then dispersed in the second mass of the organic solvent to obtain the above-mentioned solid electrolyte slurry.

[0056] The embodiment of the present application determines the mass of each component according to the solid content and the ratio between the components, so that the quality of the preparation process can be accurately controlled, thereby achieving better utilization of the second phase inorganic material.

[0057] Optionally, the organic solvent includes xylene solvent, acetonitrile, N-methylpyrrolidone (NMP), acetone, tetrahydrofuran (THF), toluene, DMSO (dimethyl sulfoxide) and DMF (dimethylformamide) mixed solvent, etc., preferably xylene solvent.

[0058] Optionally, the mixing method can be any one of ultrasound, stirring or ball milling. Preferably, ball milling is used. When ball milling is used for mixing, the ball milling parameters can be: 0.1-5h, rotation speed 100-500rpm, temperature room temperature.

[0059] S50: performing coating treatment, drying treatment and hot pressing treatment on the solid electrolyte slurry to obtain the solid electrolyte film.

[0060] For example, the solid electrolyte slurry can be coated onto the surface of the aluminum foil, followed by drying and hot pressing to obtain a solid electrolyte film.

[0061] Optionally, the temperature of the drying treatment is 50°C-90°C, and the time is 1h-24h.

[0062] In the embodiment of the present application, a solid electrolyte and a second-phase inorganic material are mixed to obtain a mixed powder; in the mixed powder, the mass ratio of the solid electrolyte to the second-phase inorganic material is 1: (0.1wt% to 30wt%); the mixed powder and the binder are dispersed in an organic solvent to obtain a solid electrolyte slurry; the solid electrolyte slurry is coated, dried and hot-pressed to obtain a solid electrolyte film, thereby using the second-phase inorganic material phase change method to improve the density of the electrolyte film layer. Specifically, the second-phase inorganic material can melt quickly when heated and flow when pressurized, so that it can fill the defects in the electrolyte powder film layer, thereby improving the density of the electrolyte film layer, and obtaining a substantially completely dense, void-free solid electrolyte film layer, thereby reducing the short-circuit risk of the all-solid-state battery. Secondly, the above-mentioned preparation method has the advantages of simple operation and low cost, and will not affect the high-resistance phase inside the solid electrolyte film, basically maintaining the original high ionic conductivity, and can also reduce the short-circuit risk of the all-solid-state battery.

[0063] In some embodiments, the second phase inorganic material includes at least one of LiFSI and KFSI;

[0064] In the case where the second-phase inorganic material includes LiFSI and KFSI, a molar ratio of the LiFSI to the KFSI ranges from (0 to 100): (100 to 0).

[0065] For example, LiFSI, the full name of which is lithium bis(fluorosulfonyl)imide, is a fluorine-containing lithium salt with high decomposition temperature, high conductivity and more stable performance to moisture, and its melting point is 124°C. KFSI, potassium bis(fluorosulfonyl)imide, has properties such as high salt diffusion coefficient, cation transfer number, high ion conductivity, and its melting point is 102°C. All of the above materials can melt quickly when heated and flow when pressurized, so that they can fill the defects in the electrolyte powder film layer, thereby improving the density of the electrolyte film layer.

[0066] When the second phase inorganic material includes LiFSI and KFSI, the melting point of the mixture is around 65°C. For example, when the molar ratio of LiFSI and KFSI is 0.45:0.55, the melting point is 65°C, and when the molar ratio is 41:59, the melting point is 72°C, which is consistent with the operating temperature range of hot pressing treatment.

[0067] In the embodiment of the present application, at least one of LiFSI and KFSI is used as the second phase inorganic material, which not only has the advantage of low cost, but also utilizes the fact that the two materials have a suitable melting point after being mixed, can melt quickly during hot pressing treatment, and can flow when pressurized, so that it can fill the defects in the electrolyte powder film layer, thereby improving the density of the electrolyte film layer.

[0068] In some embodiments, Figure 3 As shown, in the case where the second-phase inorganic material includes the LiFSI and the KFSI, before the above step S50, the method further includes:

[0069] S41: Determine the molar ratio of the LiFSI and the KFSI.

[0070] S42: Determine the melting point of the second-phase inorganic material based on the molar ratio of the LiFSI to the KFSI.

[0071] S43: Based on the melting point, determine the hot pressing method and corresponding hot pressing parameters; the hot pressing method includes at least one of roller pressing, flat plate pressing, and isostatic pressing.

[0072] Exemplarily, when the second-phase inorganic material in the prepared solid electrolyte slurry includes LiFSI and KFSI, the melting point of the second-phase inorganic material can be obtained according to the molar ratio of LiFSI and KFSI, so that the hot pressing method and the corresponding hot pressing parameters can be determined according to the melting point. The principle for determining the hot pressing method and the corresponding hot pressing parameters is: to ensure that the second-phase inorganic material can melt and flow during the hot pressing process to ensure that the defects in the electrolyte powder film layer are filled.

[0073] In some embodiments, the hot pressing parameters corresponding to the flat plate pressing and the isostatic pressing include hot pressing temperature, hot pressing pressure and hot pressing time; the hot pressing temperature is 70° C. to 130° C.; the hot pressing pressure is 100 MPa to 1000 MPa; the hot pressing time is 1 min to 100 min;

[0074] The hot pressing parameters corresponding to the roller pressing include roller pressing pressure and roller pressing temperature; the roller pressing pressure is 10 kN / m to 150 kN / m; and the roller pressing temperature is 70-130°C.

[0075] The embodiment of the present application determines the melting point according to the molar ratio of LiFSI and KFSI, so that a suitable hot pressing treatment method and corresponding hot pressing parameters can be selected according to the melting point, and the phase change properties of the second phase inorganic material can be better utilized to make the obtained solid electrolyte film denser.

[0076] On the other hand, the embodiment of the present application also provides a solid electrolyte film, which is prepared using the above-mentioned method for preparing the solid electrolyte film. The solid electrolyte film can utilize the properties of the second phase inorganic material that can melt quickly when heated and flow when pressurized, so that it can fill the defects in the electrolyte powder film layer, thereby having the characteristics of high density and no voids. Therefore, the short circuit risk of the all-solid-state battery can be reduced. Secondly, the preparation method of the solid electrolyte film has the advantages of simple operation and low cost, and will not affect the high resistance phase inside the solid electrolyte film, basically maintaining the original high ionic conductivity, and can also reduce the short circuit risk of the all-solid-state battery.

[0077] On the other hand, the present application also provides an all-solid-state battery, wherein the all-solid-state battery comprises the above-mentioned solid electrolyte film. Figure 4 As shown, the all-solid-state battery further includes a positive electrode and a negative electrode, and the solid electrolyte film is located between the positive electrode and the negative electrode. The all-solid-state battery prepared using the solid electrolyte film reduces the risk of battery short circuit.

[0078] The application also provides a series of examples to further verify the implementation effect of the solid electrolyte film in the technical solution of the application. The implementation effect of the technical solution of the application is described in detail below in combination with specific examples.

[0079] Embodiment 1:

[0080] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0081] 1. Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=41:59 (molar ratio) were mixed in a ball mill at a mass ratio of 100:5 to obtain a mixed powder;

[0082] 2. Mixing the mixed powder and the binder to obtain electrolyte powder; wherein the mass of the mixed powder and the binder is the first mass, and the mass of the binder accounts for 2% of the first mass;

[0083] 3. The electrolyte powder is uniformly dispersed in a xylene solvent at a solid content of 50% to obtain a solid electrolyte slurry;

[0084] 4. The solid electrolyte slurry was coated on the surface of aluminum foil and dried at 60°C for 1 hour to form a 50 μm thick dry film;

[0085] 5. The dry film is subjected to static pressure treatment with parameters of 80°C-600MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0086] Embodiment 2:

[0087] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0088] 1. Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=41:59 (molar ratio) were mixed in a ball mill at a mass ratio of 100:0.1 to obtain a mixed powder;

[0089] Steps 2-5 are exactly the same as in Example 1.

[0090] Embodiment 3:

[0091] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0092] The Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=41:59 (molar ratio) were mixed in a ball mill at a mass ratio of 100:30 to obtain a mixed powder;

[0093] Steps 2-5 are exactly the same as in Example 1.

[0094] Example 4

[0095] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0096] 1. Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=100:0 (molar ratio) were mixed in a ball mill at a mass ratio of 100:5 to obtain a mixed powder;

[0097] Steps 2-4 are exactly the same as in Example 1;

[0098] 5. The dry film is subjected to static pressure treatment with parameters of 130°C-600MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0099] Example 5

[0100] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0101] 1. Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=0:100 (molar ratio) were mixed in a ball mill at a mass ratio of 100:5 to obtain a mixed powder;

[0102] Steps 2-4 are exactly the same as in Example 1;

[0103] 5. The dry film is subjected to static pressure treatment with parameters of 105°C-600MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0104] Example 6

[0105] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0106] Steps 1-4 are exactly the same as in Example 1;

[0107] 5. The dry film is subjected to static pressure treatment with parameters of 70°C-600MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0108] Example 7

[0109] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0110] Steps 1-4 are exactly the same as in Example 1;

[0111] 5. The dry film is subjected to a flat plate pressing process with parameters of 80°C-600MPa-5min to obtain a 30um solid electrolyte film with high density attached to the surface of the aluminum foil.

[0112] Example 8

[0113] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0114] Steps 1-4 are exactly the same as in Example 1;

[0115] 5. The dry film is subjected to roller pressing at a parameter of 80°C-100 kN / m to obtain a high-density 30 um solid electrolyte film attached to the surface of the aluminum foil.

[0116] Example 9

[0117] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0118] Steps 1-4 are exactly the same as in Example 1;

[0119] 5. The dry film is subjected to isostatic pressing with parameters of 80°C-100MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0120] Example 10

[0121] The present invention provides a solid electrolyte film and a preparation method thereof. The specific preparation method includes:

[0122] 5. The dry film is subjected to isostatic pressing with parameters of 80°C-1000MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0123] Comparative Example 1:

[0124] This comparative example 1 provides a solid electrolyte film and a preparation method thereof, and the specific preparation method includes:

[0125] 1. Mixing Li6PS5Cl electrolyte and SBR binder to obtain electrolyte powder; wherein the mass ratio of Li6PS5Cl electrolyte to SBR binder is 100:2;

[0126] 2. The electrolyte powder is uniformly dispersed in a xylene solvent at a solid content of 50% to obtain a solid electrolyte slurry;

[0127] 3. The solid electrolyte slurry was coated on the surface of the aluminum foil and dried at 60°C for 1 h to form a 50 μm thick dry film;

[0128] 4. The dry film was subjected to isostatic pressing with parameters of 80°C-600MPa-5min to obtain a 30um solid electrolyte film attached to the surface of the aluminum foil.

[0129] Comparative Example 2:

[0130] This comparative example 1 provides a solid electrolyte film and a preparation method thereof, and the specific preparation method includes:

[0131] Steps 1-3 are exactly the same as in Example 1;

[0132] 4. The dry film was subjected to isostatic pressing with parameters of 60°C-600MPa-5min to obtain a 30um solid electrolyte film attached to the surface of the aluminum foil.

[0133] Comparative Example 3:

[0134] 1. Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=41:59 (molar ratio) were mixed in a ball mill at a mass ratio of 100:40 to obtain a mixed powder;

[0135] Steps 2-5 are exactly the same as in Example 1.

[0136] Comparative Example 4:

[0137] Steps 1-4 are exactly the same as in Example 1;

[0138] 5. The dry film is subjected to static pressure treatment with parameters of 80°C-50MPa-5min to obtain a high-density 30um solid electrolyte film attached to the surface of the aluminum foil.

[0139] In the implementation of this application, the difference between Example 2 and Example 1 is that the mass ratio of Li6PS5Cl electrolyte and the second phase low melting point lithium salt is 100:0.1, and the other conditions are the same as in Example 1; the difference between Example 3 and Example 1 is that the mass ratio of Li6PS5Cl electrolyte and the second phase low melting point lithium salt is 100:30, and the other conditions are the same as in Example 1; the difference between Example 4 and Example 1 is that the second phase low melting point lithium salt LiFSI:KFSI=100:0 (molar ratio), the isostatic pressing temperature is 130°C, and the other conditions are the same as in Example 1; the difference between Example 5 and Example 1 is that the second phase low melting point lithium salt LiFSI:KFSI=0:100 (molar ratio), the isostatic pressing temperature is 105°C, and the other conditions are the same as in Example 1; the difference between Example 6 and Example 1 is that the isostatic pressing temperature is 70°C; the difference between Example 7 and Example 1 is that the hot pressing treatment The method is flat plate pressing, and the other conditions are the same as those in Example 1; the difference between Example 8 and Example 1 is that the method of hot pressing treatment is roller pressing, and the roller pressing parameters are 80°C-100kN / m; the difference between Example 9 and Example 1 is that the isostatic pressing pressure is 100MPa; the difference between Example 10 and Example 1 is that the isostatic pressing pressure is 1000MPa; the difference between Comparative Example 1 and Example 1 is that no second phase inorganic material is added, and the other conditions are the same as those in Example 1; the difference between Comparative Example 2 and Example 1 is that the isostatic pressing temperature is 60°C; the difference between Comparative Example 3 and Example 1 is that the ratio of Li6PS5Cl electrolyte and the second phase low melting point lithium salt LiFSI:KFSI=41:59 (molar ratio) is 100:40 by mass ratio, and the other conditions are the same as those in Example 1; the difference between Comparative Example 3 and Example 1 is that the isostatic pressing pressure is 50MPa, and the other conditions are the same as those in Example 1.

[0140] In the examples of the present application, the solid electrolyte films prepared in the above examples and comparative examples were subjected to ion conductivity tests, scanning electron microscope tests (SEM) tests, and all-solid-state battery tests.

[0141] In the embodiments of the present application, the test method of the conductivity test is as follows: in an argon atmosphere, the upper and lower surfaces of the solid electrolyte membrane materials of some embodiments and comparative examples are respectively connected to a potentiostat equipped with a frequency response analyzer, and the ionic conductivity of the solid electrolyte material is measured by the electrochemical impedance method. The real value of the impedance at the measuring point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ionic conduction. The conductivity of the solid electrolyte film is divided by the conductivity of the electrolyte powder to obtain the conductivity retention rate.

[0142] In the embodiment of the present application, the testing method of scanning electron microscope (SEM) is: magnifying and observing the microscopic morphology of the material by scanning electron microscope (SEM). The equipment used is Sigma300-Gemini1 scanning electron microscope.

[0143] In an embodiment of the present application, the test method of the all-solid-state battery test is as follows: In an argon atmosphere, Li6PS5Cl solid electrolyte material and positive electrode active material, namely LiCoO2, are mixed in an agate mortar in a mass ratio of 30:70. These materials are mixed to obtain a positive electrode mixture. In an insulating cylinder, the positive electrode mixture and the solid electrolyte film prepared by the present invention are sequentially added to obtain a stack. A pressure of 160 MPa is applied to the stack, and then a metal Li foil (thickness of 300 μm) is stacked on the high-density electrolyte membrane layer to obtain a stack. A pressure of 5 MPa is applied to the stack to form a negative electrode. A current collector formed of stainless steel is arranged on the positive electrode and the negative electrode, and a current collecting lead is installed on the current collector. Finally, an insulating hoop is used to isolate the inside of the insulating cylinder from the external atmosphere, and the inside of the cylinder is sealed to obtain an all-solid-state battery, such as Figure 4 The battery was tested for electrochemical performance at a 3C rate in the voltage range of 2.5-4.2V.

[0144] In the examples of the present application, the test data of the solid electrolyte film obtained in the above examples and comparative examples are shown in Table 1. Figure 5-Figure 8 shown.

[0145] Table 1 Physical property test results and all-solid-state 3C rate performance of the same sample

[0146]

[0147] Figure 5 This is the surface SEM image of the dry film prepared in step 4 of Example 1. Figure 6 This is a surface SEM image of the dry film prepared in step 3 of Comparative Example 1. Figure 5 and Figure 6 In the patent, the surfaces of both are composed of irregularly arranged particles, and there are grain boundaries between the particles. These grain boundaries will be pores where lithium dendrites are easily present. When the battery charge and discharge rate is high, such as the 3C mentioned in this patent, the battery may short-circuit.

[0148] Figure 7 This is a surface SEM image of the solid electrolyte film prepared in Example 1. Figure 8 This is a surface SEM image of the solid electrolyte film prepared in Comparative Example 1. Figure 7 and Figure 8 It can be found that Figure 7The surface of the solid electrolyte film no longer has grain boundaries and pores. This is because the melting and penetration of the second-phase inorganic material repairs the original grain boundaries and cracks of the electrolyte film layer, achieving a high degree of densification of the solid electrolyte film. Figure 8 In the corresponding comparative example 1, no second phase inorganic material is added, so grain boundaries and pores still exist on its surface.

[0149] The morphology observation results, ionic conductivity retention rate and battery 3C rate short-circuit conditions of Examples 1-10 indicate that under the preparation conditions specified in the present application, solid electrolyte films with high density, high ionic conductivity retention rate and no short-circuit during 3C charge and discharge were prepared.

[0150] In Comparative Example 1, although the conductivity retention rate is relatively high, there is no pore-blocking effect due to the absence of pore-filling material, so there are still observable pores on the surface and all batteries will still be short-circuited.

[0151] Comparison of Comparative Example 2 with Example 1 shows that when the temperature of the hot pressing treatment is too low, the second phase low melting point material cannot be melted and cover the electrolyte grain boundary. Although the conductivity retention rate is high, there is no pore blocking effect and the battery will still short-circuit.

[0152] Comparative Example 3 shows that the proportion of the second phase low melting point material should not be too large, otherwise it will seriously affect the conductivity of the solid electrolyte film.

[0153] Comparative Example 4 shows that the pressure is too low to allow the molten second phase low melting point material to penetrate. Although the conductivity retention rate is high, there is no pore blocking effect and the battery will still short-circuit.

[0154] As can be seen from the embodiments provided by the present application, the present application obtains a mixed powder by mixing a solid electrolyte and a second-phase inorganic material; in the mixed powder, the mass ratio of the solid electrolyte and the second-phase inorganic material is 1: (0.1wt% to 30wt%); the mixed powder and the binder are dispersed in an organic solvent to obtain a solid electrolyte slurry; the solid electrolyte slurry is coated, dried and hot-pressed to obtain a substantially completely dense, void-free solid electrolyte film. The solid electrolyte film in the present application utilizes the second-phase inorganic material to melt quickly when heated and flow when pressurized, so that it can fill the defects in the electrolyte powder film layer, thereby improving the density of the electrolyte film layer. Secondly, it has the advantages of simple operation and low cost, and can maintain the original high ionic conductivity, reducing the short circuit risk of the all-solid-state battery.

[0155] It should be noted that the above-mentioned second phase low melting point material is a second phase inorganic material.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a solid electrolyte film, characterized in that: The preparation method comprises: The solid electrolyte and the second-phase inorganic material are mixed to obtain a mixed powder; in the mixed powder, the mass ratio of the solid electrolyte to the second-phase inorganic material is 1: (0.1wt% to 30wt%); Dispersing the mixed powder and the binder in an organic solvent to obtain a solid electrolyte slurry; The solid electrolyte slurry is subjected to coating treatment, drying treatment and hot pressing treatment to obtain the solid electrolyte film.

2. The preparation method according to claim 1, characterized in that: The second phase inorganic material includes at least one of LiFSI and KFSI; In the case where the second-phase inorganic material includes LiFSI and KFSI, a molar ratio of the LiFSI to the KFSI ranges from (0 to 100): (100 to 0).

3. The preparation method according to claim 2, characterized in that: In the case where the second-phase inorganic material includes the LiFSI and the KFSI, before the solid electrolyte slurry is subjected to coating, drying and hot pressing to obtain the solid electrolyte film, the method further includes: determining a molar ratio of the LiFSI to the KFSI; Determining a melting point of the second phase inorganic material based on a molar ratio of the LiFSI to the KFSI; Based on the melting point, the hot pressing method and corresponding hot pressing parameters are determined; the hot pressing method includes at least one of roller pressing, flat plate pressing, and isostatic pressing.

4. The method according to claim 3, characterized in that The hot pressing parameters corresponding to the flat plate pressing and the isostatic pressing include hot pressing temperature, hot pressing pressure and hot pressing time; the hot pressing temperature is 70°C to 130°C; the hot pressing pressure is 100MPa to 1000MPa; the hot pressing time is 1min to 100min; The hot pressing parameters corresponding to the rolling include rolling pressure and rolling temperature; the rolling pressure is 10 kN / m to 150 kN / m; and the rolling temperature is 70° C. to 130° C.

5. The preparation method according to claim 1, characterized in that: The sum of the masses of the binder and the mixed powder is a first mass, and the mass of the binder accounts for 0.1% to 5% of the first mass.

6. The method according to claim 1, characterized in that The solid content of the solid electrolyte slurry is 20% to 80%. The mixed powder and the binder are dispersed in an organic solvent to obtain a solid electrolyte slurry, comprising: Determining the mass of the organic solvent as the second mass according to the solid content, the mass of the mixed powder and the mass of the binder; Mixing the mixed powder and the binder to obtain electrolyte powder; The electrolyte powder is dispersed in a second mass of an organic solvent to obtain the solid electrolyte slurry.

7. The preparation method according to claim 1, characterized in that: The solid electrolyte includes Li2ZrCl6, LiNbOCl4, LiTaOCl4, Li3YCl6, Li3InCl6, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li10GeP2S12, Li2S-SiS2-Li x MO y , Li2S-P2S5-Z m S n At least one of; wherein x and y are positive numbers, M is one of P, Si, Ge, B, Al, Ga and In; m and n are positive numbers, Z is one of Ge, Zn and Ga.

8. The method according to claim 1, characterized in that: The binder includes at least one of styrene-butadiene rubber, polyacrylonitrile-butadiene, styrene-ethylene-butylene-styrene block copolymer, and styrene-ethylene-propylene-styrene block copolymer.

9. A solid electrolyte film, characterized in that: The solid electrolyte film is obtained by the preparation method of any one of claims 1 to 8.

10. An all-solid-state battery, characterized in that: Comprising the solid electrolyte film according to claim 9.